The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1055/s-0034-1393957
|View full text |Cite|
|
Sign up to set email alerts
|

Predictors of Success in the Treatment of Obstructive Sleep Apnea Syndrome with Mandibular Repositioning Appliance: A Systematic Review

Abstract: Introduction Obstructive sleep apnea syndrome affects up to 4% of middle-aged men and 2% of adult women. It is associated with obesity. Objective The objective of this article is to review the literature to determine which factors best correlate with treatment success in patients with obstructive sleep apnea syndrome treated with a mandibular repositioning appliance. Data Synthesis A search was performed of the PubMed, Cochrane, Lilacs, Scielo, and Web of Science databases of articles published from January 19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…Nevertheless, the clinical utility of cephalometric measurements in the prediction of MAD treatment outcomes in OSA remains controversial. A recently published review by Saffer et al 11 found no clear predictors of MAD treatment success. However, cephalometric and anatomical factors were not investigated because no randomized controlled trials addressing this issue were included in the review.…”
Section: Introductionmentioning
confidence: 98%
“…Nevertheless, the clinical utility of cephalometric measurements in the prediction of MAD treatment outcomes in OSA remains controversial. A recently published review by Saffer et al 11 found no clear predictors of MAD treatment success. However, cephalometric and anatomical factors were not investigated because no randomized controlled trials addressing this issue were included in the review.…”
Section: Introductionmentioning
confidence: 98%
“…However, other studies have suggested that younger age, lower BMI, smaller upper airways, less collapsibility in the upper airways, high hyoid bone position, and non-REM dominated and nonpositional OSA may be more important than Friedman score for predicting AHI improvement in MAS treatment [11,19,29]. Nevertheless, there are still uncertainties regarding the significance of predictors in successful MAS treatment [19,36]. erefore, Friedman score cannot be used to decide whether CPAP or MAS treatment is the most suitable for individual patients with nonsevere OSA.…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al [3] did not describe the types of OA, and hence those SRs were excluded. Ultimately, 27 articles were included [1,[4], [5], [6], [7], [8], [9], [10], [11], [12], [13], [14], [15], [16], [17], [18], [19], [20], [21], [22], [23], [24], [25], [26], [27], [28], [29]]. Descriptions of the included SRs are shown in Table 1.…”
Section: Review Of Srsmentioning
confidence: 99%
“…Breakdown of the content of the 27 SRs is as follows: there were 10 articles on comparison with other treatments [1,9,12,13,[18], [19], [20],22,24,27], five articles on the types of OAm [5,6,14,16,21], and six articles on the effect of OAm and the associated side effects [4,8,23,26,28,29]. There were also three articles on predicting the therapeutic effect of OAm [10,11,15], two articles on changes in the upper respiratory tract caused by this therapy [7,25], and one article on a remotely controlled mandibular positioner [17]. The SR by Okuno et al [15] based on predicting the therapeutic effects of OAm was the latest.…”
Section: Review Of Srsmentioning
confidence: 99%